2022
DOI: 10.15625/0866-7136/16834
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent behavior of a MEMS microbeam under electrostatic actuation

Abstract: The size-dependent behavior of a silicon microbeam with an axial force in MEMS is studied using a nonlinear finite element procedure. Based on a refined third-order shear deformation theory and the modified couple stress theory (MCST), nonlinear differential equations of motion for the beam are derived from Hamilton’s principle, and they are transferred to a discretized form using a two-node beam element. Newton-Raphson based iterative procedure is used in conjunction with Newmark method to obtain the pull-in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The beam deflection and the pull-in voltage were determined using the modified variational iteration method. Le et al [14] presented a MCST based finite element formulation for assessing frequencies and pull-in voltages of microbeams subjected to electrostatic force. Their numerical investigation showed that the deflections are overestimated while the pull-in voltages are underestimated by ignoring the microsize effect.…”
Section: Introductionmentioning
confidence: 99%
“…The beam deflection and the pull-in voltage were determined using the modified variational iteration method. Le et al [14] presented a MCST based finite element formulation for assessing frequencies and pull-in voltages of microbeams subjected to electrostatic force. Their numerical investigation showed that the deflections are overestimated while the pull-in voltages are underestimated by ignoring the microsize effect.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method agreed with literature values to within 4%. Recently, Le et al [23] studied the size dependent behavior of a MEMS microbeam under electrostatic actuation using the improved third-order shear deformation theory of Shimpi and Patel [24]. The authors concluded that the dynamic deflections of the beam are overestimated when ignore the microsize effect.…”
Section: Introductionmentioning
confidence: 99%